INCREASING STUDENTS’ RESPONSIBILITY AND SCIENTIFIC CREATIVITY THROUGH CREATIVE RESPONSIBILITY BASED LEARNING - Suyidno, Suyidno; Susilowati, Eko; Arifuddin, Muhammad; Misbah, Misbah; Sunarti, Titin; Dwikoranto, Dwikoranto (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
Scientific creativity and responsibility are believed to be key factors for overcoming increasingly complex real-life problems faced by students; but both competencies are not trained in school. Therefore, this research aims to describe the effectiveness of creative responsibility based learning (CRBL) to increase student?s responsibility and scientific creativity on physics learning in senior high school. This research used one group pretest-posttest design involving 66 students of two senior high schools in Banjarmasin, South Kalimantan, Indonesia. The data collection was conducted by using responsibility observation emphasizing on participatory, cooperation, delivering an opinion, and leadership. Additionally, data were gained through scientific creativity test emphasizing on problem finding, product improvement, scientific imagination, scientific problem solving, and creative product design. The data analysis was done through qualitative descriptive, n-gain, and paired t-test. The results showed      (1) student?s responsibility for each meeting is in good criteria, and (2) there is a significant increase on students? scientific creativity at ? = 5 %, with n-gain constitutes moderate category. Thus, the CRBL is believed to be effective to increase student?s responsibility and scientific creativity in physics learning